PENGARUH DIMENSI ELECTRONIC WORD OF MOUTH PADA APLIKASI MOBILE ZOMATO TERHADAP MINAT PEMBELIAN DI WILAYAH JABODETABEK DENGAN PENDEKATAN ELABORATION LIKELIHOOD MODEL - Wayan Weda Asmara Dewi; Dian Tamitiadini; Bimo Gondokusumo (Jurnal Teknologi Informasi dan Komputer, 2016)
ABSTRACTElectronic Word Of Mouth (EWOM) is a new form of WOM since the distribution of product information or service via internet. This study focuses on online reviews about an eatery named Zomato. This study is aimed to investigate the effect of EWOM, in this case is online reviews on Zomato to the purchase intention in JABODETABEK area. Literature review of Elaboration Likelihood Model will be used in this study. In this study, both routes of Elaboration Likelihood Model are used to analyze Electronic Word Of Mouth dimension that is divided into central route and peripheral route. The independent variables on central route are information timeliness (X1), information relevance (X2), information accuracy (X3), and value added information (X4). The variables in peripheral route are information quantity (X5) and product ranking (X6). Dependent variable is the purchase intention (Y). The research method is explanative quantitative by using data collection technique via online questionnaire and use linear regression data collection technique. The most dominant and affecting variables in Electronic Word Of Mouth dimension to the purchase intention in jabodetabek area are product ranking (X6), information relevance (X2), value added information (X4), information quantity (X5), and information accuracy (X3), while information timeliness (X1) has no significant effect. Nevertheless, based on the hypothesis test, it is simultaneously that all Electronic Word Of Mouth dimension on independent variables affect to the purchase intention in Zomato in jabodetabek area.Keywords: elaboration likelihood model, electronic word of mouth, online reviews, Zomato, purchase intention.ABSTRAKElectronic Word Of Mouth (EWOM) merupakan bentuk baru dari WOM karena penyebaran informasi produk atau jasa melalui interrnet. Penelitian ini bertujuan untuk melihat pengaruh dari EWOM dalam hal ini online reviews yang terdapat pada Zomato terhadap minat pembelian di Wilayah jabodetabek. Kajian teori Elaboration Likelihood Model yang akan digunakan dalam penelitian ini. Pada penelitian ini kedua rute Elaboration Likelihood Model digunakan untuk menganalis Electronic Word Of Mouth. Variabel terdiri dari dimensi Electronic Word Of Mouth dibagi kedalam rute sentral dan rute perferal. Variabel independen pada rute sentral terdiri dari information timeliness (X1), information relevance (X2), information accuracy (X3), dan value added information (X4). Sedangkan variabel pada rute periferal information quantity (X5) dan product ranking (X6). Variabel dependen adalah minat pembelian (Y). Jenis penelitian yang digunakan adalah eksplanatif kuantitatif dengan teknik pengumpulan data melalui kuesioner online dan menggunakan teknik analisis data regresi linier berganda. Dimensi Electronic Word Of Mouth yang paling dominan dan berpengaruh pada Zomato terhadap minat pembelian di Wilayah JABODETABEK adalah product ranking (X6), information relevance (X2), value added information (X4), information quantity (X5), dan information accuracy (X3) sedangkan information timeliness (X1) tidak memiliki pengaruh yang signifikan. dan pada variabel indepeden memiliki pengaruh pada Zomato terhadap minat pembelian di Wilayah jabodetabek.Kata Kunci: elaboration likelihood model, electronic word of mouth, , online reviews, zomato, minat pembeli.